Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1103/physrevd.66.034502
|View full text |Cite
|
Sign up to set email alerts
|

Lattice artifacts and the running of the coupling constant

Abstract: We study the running of the Lüscher-Weisz-Wolff (LWW) coupling constant in the two dimensional O(3) nonlinear σ model. To investigate the continuum limit we refine the lattice spacing from the 1 16 value used by LWW up to 1 160 . We find much larger lattice artefacts than those estimated by LWW and that most likely the coupling constant runs slower than predicted by perturbation theory. A precise determination of the running in the continuum limit would require a controlled ansatz of extrapolation, which, we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The choice of the abscissa 1/(ln L + c), was motivated by the fact that in studying lattice artefacts for the LWW step scaling function we found that such an ansatz seemed to describe the data pretty well (see ref. [12] Fig.7). The value of the parameter c = 0.7 was obtained from a joint fit to our O(3) and icosahedron data with a common limiting value for L → ∞; it is of acceptable quality (χ 2 /dof = 11.6/8).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The choice of the abscissa 1/(ln L + c), was motivated by the fact that in studying lattice artefacts for the LWW step scaling function we found that such an ansatz seemed to describe the data pretty well (see ref. [12] Fig.7). The value of the parameter c = 0.7 was obtained from a joint fit to our O(3) and icosahedron data with a common limiting value for L → ∞; it is of acceptable quality (χ 2 /dof = 11.6/8).…”
mentioning
confidence: 98%
“…The choice of the abscissa 1/(ln L + c), was motivated by the fact that in studying lattice artefacts for the LWW step scaling function we found that such an ansatz seemed to describe the data pretty well (see ref. [12] Fig. 7).…”
mentioning
confidence: 98%